PENGARUH MICROTEACHING TERHADAP KECEMASAN CALON GURU DALAM PROSES PEMBELAJARAN DI UNIVERSITAS MUHAMMADIYAH ACEH - Helmanda, Cut Mawar; Nazariah, Nazariah; Yani, Muhammad; Salsabila, Siti (Jurnal Dedikasi Pendidikan, 2025)
This research aims to determine the effect of microteaching on the anxiety of prospective teachers in the learning process at University of Muhammadiyah Aceh. This study employs a mixed-methods approach, encompassing both quantitative and qualitative methods. The population of this research consists of students from the Faculty of Islamic Studies at University of Muhammadiyah Aceh, academic year of 2021, who were taking the microteaching course, with a sample size of 20 students. The data collection techniques used included questionnaires and interviews. The data analysis technique used to answer the research questions were normality, linearity and linear regression tests. The results of the study showed that microteaching learning was very meaningful for prospective teacher students in overcoming and reducing their anxiety levels in preparing to teach in front of the class with a strong correlation level and a determination coefficient of 43.2%. This indicates that the microteaching learning variable's ability to influence the anxiety variable of prospective teacher students is 43.2%. The results of this study indicated that there is an effect of microteaching on the anxiety of prospective teachers in the learning process at University of Muhammadiyah Aceh. Furthemore, the feedback from the lecturer and the students helped the performer to deal with the anxiety for the upcoming teaching performance